The von Neumann Facet and the Turnpike Properties for a Neoclassical Optimal Growth Model with Many Capital Goods II - Harutaka Takahashi (Queen's University, Department of Economics, 1995)
We will study a multi-sector discrete-time optimal growth model with a neoclassical non-joint technology and show the Neighborhood Turnpike; any optimal path will be trapped in the neighborhood of an associated optimal steady state and its neighborhood can be chosen as small as possible by taking the discount factor close enough to one and the full Turnpike; any optimal path converges to an associated optimal steady state path when discount factors are close enough to one. These two Turnpike properties will provide the firm theoretical background for an application of a neoclassical optimal growth model with heterogeneous capital goods to economic analyses.
Keywords: 330